DECREASED PERFORMANCE AT UNSIGNALED INTERSECTIONS AFFECTS THE CONSTRUCTION OF THE SOLO-YOGYA ROAD WITH THE LEAST SQUARE METHOD - Hermani, Wahyuningsih Tri; Setyawan, Ary; Syafi’i; Gravitiani, Evi (Journal of Applied Engineering Science, 2023)
The construction of the Solo-Yogyakarta toll road is part of the National Strategic Project. At the development stage, toll road infrastructure needs to assess the impact of traffic, considering many security and safety disturbances. Road performance evaluation is essential to overcome traffic problems during toll road operations in the future. The purpose of the study was to calculate traffic performance at the unsignaled intersection affecting the construction of the Solo-Yogya toll road. The locations studied were four Solo-Yogya toll road access intersections using primary data on the condition of existing non-toll roads. Carry out traffic surveys of the number of vehicles, travel time, and vehicle speed. The performance of the unsignaled intersection was calculated using Jica Strada’s modeling with applicable toll road tariffs and traffic growth of 5.6% per year. The performance of the unsignaled intersection at the construction of the Solo-Yogya toll road in 2022 has an average Volume-Capacity Ratio (VCR) value of 0.61. In 2046, it has an average Volume-Capacity Ratio value of 0.99. At the intersection of Boyolali-Kartosuro-Banyudono and the intersection Kartosuro-Klaten-Ngaron, it is recommended to make an Interchange before 2032. The recommendation for making the Kartosuro and Boyolali Interchange is because in 2032 the Volume-Capacity Ratio is more than 0.8 to reduce vehicle delays.